HISTOCHEMICAL STUDIES ON THE EFFECT OF ZINC DEFICIENCY IN ' THE RAT OVARY - H. Ghaeb, R.; Y. S. Haddad , F.; T. Al-Azzawi , H. (The Iraqi Journal of Veterinary Medicine, 1990)
Adult female rats were given a zinc deficient diet for six weeks. During this period their ovaries were compared with those of» normally fed rats. The histochemical activities of two zinc metalloenzymes, namely alkaline phosphatase (APase) and carbonic anhydrase (CA) were markedly lowered three and two weeks after starting feeding, respectively. lg vitro, reactivation to the control level of activity of both enzymes by exogenous zinc added to the incubation medium suggests absence of zinc from the apoenzymes-is the cause of decreased activity rather than decreased synthesis of the apoenzymes.